Radiotherapy and surgery remain effective treatment options for retroperitoneal MPNST: a retrospective study based on SEER database - Xi, Zhe; Aobo, Zhuang; Li, Xi; Yue, Wang; Yan, Guangting; Lin, Zhenhang; Zhang, Geng; Xia, Xiaogang; Lian, Lanlan; Li, Wengang (Frontiers in Surgery, 2024)
Abstract: The proportion of retroperitoneal malignant peripheral nerve sheath tumours (RMPNST) in retroperitoneal tumors is less than 5%, but the mortality rate is very high. However, there is no relevant research focused on RMPNST only. We retrospectively analyzed data from the SEER database of patients with primary RMPNST from 2000 to 2019, by leveraging the advantages of the Seer database, we can explore the prognosis of such rare diseases. Kaplan-Meier method was used to construct the survival curve, and cox regression model was used to analyze the factors affecting the prognosis of patients. In addition, a model was developed to distinguish high-risk and low-risk patients. This study included a total of 52 patients, with a median survival time of 39 months (95% CI 12.740-65.260) and a 5-year survival rate of 44.2% (95% CI 0.299-0.565). Radiotherapy (p=0.004, OR: 1.475, 95% CI 0.718-3.033), metastasis disease (p=0.002, OR: 5.596, 95% CI 2.449-47.079) and surgery (p=0.003, OR: 5.003, 95% CI 0.011-0.409) were associated with overall survival (OS). The 5-year distant metastasis rate was 36% (95% CI 0.221-0.499). We used the above risk factors to separate patients into high and low groups and evaluate the results through the receiver operating characteristic (ROC) curve. This model is beneficial for guiding the selection of treatment strategies. The majority of RMPNST patients have a good prognosis after surgery, and the establishment of high-low group is helpful for clinical decision-making.